Revisiting the Perception of Silence in Linguistics - AL-Jahdhami, Said (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
Silence in human communication has not only been marginalized as a means of communication, but has often been considered as void of serving any communicative role. It is presumptuously viewed as the mere opposite of communication occurring at the far end of the communicative continuum. Investigating the role of silence in human communication from a linguistic point of view, this paper, hence, attempts to show that such conventional view of silence as a non-communicative tool should be reconsidered. It argues that both silence and speech make an integral part of human communication as they coincide in any delivered message. The context in which they serve a communicative function plays a major role in their use, the choice of one over the other, as well as the interpretation of any delivered message. The study also argues that speech and silence do not always fall into the traditional schematic classification of vocal versus non-vocal. While silence can be vocal in some occasions in human communication, speech can be expressed non-vocally too.